Studi Instalasi Penerangan Jalan Layang Lenteng Agung, Kecamatan Jagakarsa, Jakarta Selatan - OKTAVIAN, WILLY; HARYANTO, NASRUN (e-Proceeding FTI, 2024)
Public street lighting (PJU) is a very important aspect in structuring an area/city. Especially at night, when the road is dark, lighting is needed so that the driver can see well and recognize an object accurately. The lighting system at the PJU requires careful planning in conducting a calculation study including the amount of power, line current, voltage drop and lighting intensity. The purpose of this study was to determine the value of the voltage drop with a conductor length of 480 meters for the south side and 540 meters for the north side and determine the value of the intensity of illumination using DIALux evo 9.1 software. In the calculation, the voltage drop values are 0.76 volts (minimum) and 5.27 volts (maximum). The width of Jalan Lenteng Agung is 6.5 meters. The planned number of light points is 34 light points with a pole height of 11 meters and a distance between poles of 30 meters and using 120 watt LED lights with a lumen of 14400 lm. The intensity of illumination obtained is 22.81 lux. Keywords : dialux evo 9.1, tensitas cahaya, lampu LED, penerangan jalan umum, tegangan jatuh. ABSTRAK Penerangan jalan umum (PJU) merupakan aspek yang sangat penting dalam penataan suatu daerah/kota. Khususnya pada malam hari, keadaan jalan gelap maka dibutuhkan suatu peneragan agar pengendara dapat melihat dengan baik dan mengenali suatu objek dengan akurat. Sistem peneragan pada PJU membutuhkan perencanaan secara teliti dalam melakukan studi perhitungan meliputi jumlah daya, arus saluran, tegangan jatuh dan intensitas peneragan. Tujuan dari penelitian ini adalah untuk mengetahui besarnya nilai tegangan jatuh dengan panjang penghantar 480 meter untuk sisi selatan dan 540 meter untuk sisi utara dan mengetahui nilai intensitas peneragan dengan menggunakan software DIALux evo 9.1. Pada perhitungan didapatkan nilai tegangan jatuh sebasar 0,76 volt (minimum) dan 5,27 volt (maksimum). Lebar jalan lenteng agung adalah 6,5 meter. Jumlah titik lampu yang direncanakan 34 titik lampu dengan tinggi tiang 11 meter dan jarak antar tiang 30 meter dan menggunakan lampu LED 120 watt dengan lumen 14400 lm. Intensitas penerangan yang diperoleh 22,81 lux. Kata kunci : dialux evo 9.1, tensitas cahaya, lampu LED, penerangan jalan umum, tegangan jatuh.